Novel Gene Rearrangement in the Mitochondrial Genome of Three Garra and Insights Into the Phylogenetic Relationships of Labeoninae - Zhang, Chi; Zhang, Kun; Peng, Ying; Zhou, Jianshe; Liu, Yifan; Liu, Bingjian (Frontiers in Genetics, 2022)
Complete mitochondrial genomes (mitogenomes) can provide valuable information for phylogenetic relationships, gene rearrangement, and molecular evolution. Here, we report the mitochondrial whole genomes of three Garra species and explore the mechanisms of rearrangements that occur in their mitochondrial genomes. The lengths of the mitogenomes’ sequences of Garra dengba, Garra tibetana, and Garra yajiangensis were 16,876, 16,861, and 16,835, respectively. They contained 13 protein-coding genes, two ribosomal RNAs, 22 transfer RNA genes, and two identical control regions (CRs). The mitochondrial genomes of three Garra species were rearranged compared to other fish mitochondrial genomes. The tRNA-Thr, tRNA-Pro and CR (T-P-CR) genes undergo replication followed by random loss of the tRNA-Thr and tRNA-Pro genes to form tRNA-Thr, CR1, tRNA-Pro and CR2 (T-CR-P-CR). Tandem duplication and random loss best explain this mitochondrial gene rearrangement. These results provide a foundation for future characterization of the mitochondrial gene arrangement of Labeoninae and further phylogenetic studies.